(untitled) (Transport systems and technologies, 2022)
The paper reviews shunting electric locomotives, the use of which is becoming widespread due to lower costs of fuel and energy resources and a reduction in the impact on the environment. Mathematical models of the movement of a train with a shunting electric locomotive have been developed. A four-axle electric locomotive with a power of 750 kW is proposed for research. A mathematical model of the movement of a train with a ChME3 diesel locomotive has been developed. To compare the costs of fuel and energy resources for freight and transfer operations, simulations of train movement were carried out on sections of the route Kharkiv-Sortuvalny – Merefa and Kharkiv-Sortuvalny – Lyubotyn with different numbers of cars. The simulation was carried out for movement with a shunting electric locomotive and a ChME3 diesel locomotive. It was established that the costs of fuel and energy resources in the case of using a shunting electric locomotive are 2.5-3 times lower compared to a ChME3 diesel locomotive. Based on the obtained results, it is proposed to use dual mode locomotives for the renewal of shunting rolling stock for electrified sections of railways. The locomotive must be equipped with an energy-efficient electric drive and a combined power plant based on a modern diesel engine or other primary energy source in combination with an on-board energy storage system and intelligent management of energy flows in the traction system.